Nelumbo nucifera Lotus, Sacred Lotus: FPS424/FP424, 6/2007 - Gilman, Edward (EDIS, 2007)
This document provides an overview of Nelumbo nucifera, commonly known as the Sacred Lotus. It describes the plant’s physical characteristics, including its large, round leaves and fragrant pink or white flowers. The document highlights the plant’s adaptability to various water conditions and its ability to thrive in muddy, murky environments. It also outlines the plant’s cultural and religious significance, particularly in Buddhism and Hinduism, where it symbolizes purity and spiritual enlightenment. Additionally, the document notes the plant’s uses in traditional medicine and its potential invasiveness in non-native regions. Original publication date September 1999.